The Relevance of Muhammad 'Abid Al-Jabiri John Locke's Thoughts about Islamic Education - Ahmad Syaifuddin; Irfan Hania (LPPM STIT Nurussalam OKU Timur. Sidogede, Kec. Belitang, Kabupaten Ogan Komering Ulu Timur, Sumatera Selatan 32382, 2023)
The purpose of this study is to examine the relevance of the concept of Islamic education from al-Jabiri's thought which has characteristics with its Islamic style and John Locke with its empiricism. This research is literature-based research with a qualitative approach. The data obtained in this study come from books, research in the form of scientific articles, as well as studies that have been conducted by previous researchers related to the thoughts of al-Jabiri and John Locke on Education. The results of this study show that Islamic Education in the intellectual aspect, the aspect of faith development, and the skill aspect, both from the Al-Jabiri concept with its Islamic style or John Locke with its empiricism both require that children be given guidance and direction to be able to achieve learning goals because student are still easily influenced by the environment around them. The concept of Islamic Education desired by al-Jabiri and John Locke is not only to give the material in the form of mere memorization but must also be guided and directed as humans in general so that they are not affected by the environment and associations that exist around student. Keywords: Relevance, Islamic Education, Al-Jabiri, John Locke.